Un vistazo al Derecho Constitucional a través del Derecho Internacional. Entrevista a Juan José Ruda Santolaria - Monge Morales, Gonzalo J. (Pontificia Universidad Católica del Perú, 2015)
What is the normative status of a treaty in Peruvian domestic law? What would happen at theinternational level if the Peruvian ConstitutionalCourt declared  a treaty to be unconstitutional? How to interpret Peruvian maritime domain, asrecognized in our Constitution, after the ruling of the International Court of Justice on the maritimedifferendum with Chile?These issues don’t only concern Constitutional Law; thus, in this interview, the renowned professor provides us with, from the standpoint of International Law, answers about these and other issues, but he also illustrates us about the implications for Peru of the aforementioned Court’sruling, delivered more than a year ago.

¿Cuál es el rango normativo de un tratado en el Derecho interno peruano?  ¿Qué ocurriría en el ámbito internacional si el Tribunal Constitucional peruano  declarara inconstitucional un tratado?¿Cómo entender el dominio marítimo del Perú, reconocido en nuestra Constitución, luego del fallode la Corte Internacional de Justicia sobre el diferendo marítimo con Chile?Estas cuestiones no pertenecen únicamente al Derecho Constitucional; por ello, en la presente entrevista, el reconocido profesor nos brinda desde el Derecho Internacional respuestas sobre estos y otros temas, así como también nos ilustra acerca de las implicancias para el Perú del mencionado fallode la Corte, a más de un año de haber sido dictado.
A look at Constitutional Law through International Law. Interview with Juan José Ruda Santolaria
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01